Cholecysto-hepatic duct serving as the only drainage pathway of bile from the intrahepatic to the extrahepatic biliary system in an infant: a case report - Samin Khoei; Payam Riahi Samani; Faezeh Fazelnia; Neda Pak (BMC, 2022)
Abstract Background Cholecystohepatic duct is a rare anomaly of the biliary system which involves drainage of bile into the gallbladder which may be associated with agenesis of the common hepatic duct or common bile duct. Case presentation A 2.5-month-old infant presented to our emergency department with icterus. He had a history of esophageal atresia and imperforate anus which had been treated surgically by thoracotomy, esophagostomy, gastrostomy and colostomy placement. Following imaging studies by ultrasound and MRCP, the diagnosis of common hepatic duct agenesis was made. Cholecystohepatic duct was present as the solitary drainage pathway of bile from the intrahepatic to extrahepatic biliary system. Conclusions Cholecystohepatic ducts need a high index of suspicion to be diagnosed on preoperative hepatobiliary imaging. As they may be asymptomatic, they are predisposed to iatrogenic injury during hepatobiliary surgeries.